1
$\begingroup$

We say that a module $M$ is indecomposable if for $M=M_{1} +M_{2}$ (not direct sum) we have that $M_{1}=M$ or $M_{2}=M$. Let $\sigma:P \to M$ a projective cover of $M$, this means that $\sigma$ is an epimorphism and $\ker(\sigma)$ is superfluous on $P$ which means that if there is some $P_{1} \leq P$ such $P_{1} + \ker(\sigma)=P$ then $P_{1}=P$ and $M$ semi-perfect, i.e, every quotient of $M$ has a projective cover, I want to prove that if P is indecomposable then $M$ is indecomposable.

Lets take $M$ such $M=M_{1} +M_{2}$ and as $P$ is projective and $M$ semiperfect I got by some result I found that every submodule of $P$ is supplemented which means that for every $P_{1} \leq P$ there is some $P' \leq P$ such $P_{1} +P' =P$, so considering $\ker(\sigma)$ and its suplement $P'$ we have that $P'+\ker(\sigma)=P$ but as $\ker(\sigma)$ is superfluous , $P'=P$. So $\sigma(P)=\sigma(P')= M=M_{1} +M_{2}$ but I don't see how to get $M_{1}=M$ or $M_{2}=M$....

Also with my general hypothesis I got that $P$ is indecompsable in the way I mean it first is equivalent to be directly indecomposblae (direct sum) but I don't know if this helps.

$\endgroup$
  • 1
    $\begingroup$ I have recently found that what Kasch calls an indecomposable module is usually called a hollow module, namely one that cannot be expressed as a sum of proper submodules. $\endgroup$ – Zeek May 29 at 0:07
  • $\begingroup$ Exactly! You helped me by proving this for directly indescomposable according to Kasch. With the general hypothesis M indescomposable implies M indescomposable but not the other implication. @zeek $\endgroup$ – Cos May 29 at 2:42
1
$\begingroup$

More generally we have the following:

Let $f:M \twoheadrightarrow N$ a surjection of $R$-modules with superfluous kernel. If $M$ is indecomposable then $N$ is indecomposable.

Proof: Suppose for the sake of contradiction that $N = N_1 + N_2$ with $N_1, N_2 \not= N$. Set $M_i = f^{-1}(N_i)$, so $M_i$ is a proper submodule of $M$, and is superfluous because $M$ is indecomposable. Also note that $f(M_1 + M_2) = N_1 + N_2 = N$. Recall that a surjective morphism of modules $M \twoheadrightarrow N$ has superfluous kernel iff $f(M') \not= N$ for every submodule $M' \subsetneq M$, and thereby conclude that $M_1 + M_2 = M$. Thus $M$ is the sum of superfluous submodules, which is absurd.

|-------EDIT--------|

Lemma Let $f: M \rightarrow N$ a surjective morphism of $R$-modules. The following are equivalent.

(1) $\ker(f)$ is a superfluous submodule of $M$.

(2) For any submodule $M'$ of $M$, $f(M') = N$ implies $M' = M$.

(3) For any module morphism $g: L \rightarrow M$, $fg$ surjective implies $g$ surjective.

Proof $(1) \implies (2)$ Let $M' \subseteq M$ with $f(M') = N$. Then for any $m \in M$ we can find $m' \in M'$ such that $f(m) = f(m')$, i.e. $m - m' \in \ker(f)$. This shows that $M' + \ker(f) = M$, and since $\ker(f)$ is superfluous, we conclude $M' = M$.

$(2) \implies (1)$ Suppose that $\ker(f) + M' = M$. Then $f(M') = f(\ker(f) + M') = f(M) = N$ and by assumption $M' = M$. Thus $\ker(f)$ is superfluous in $M'$ by definition.

$(3) \implies (2)$ If $f(M') = N$ then the composition $M' \subseteq M \rightarrow N$ is a surjection so the inclusion $M' \subseteq M$ is a surjection, aka $M' = M$.

$(2) \implies (3)$ Given $g: L \rightarrow M$ such that $fg$ is surjective, so $g(L)$ is a submodule of $M$ such that $f g(L) = N$, and by assumption $g(L) = M$, i.e. $g$ is surjective.

These concepts and facts have duals. I think it would be a nice exercise for you to work out the following.

A module is called uniform if every submodule is essential.

Exercise (A) Let $f: M \hookrightarrow N$ an injective morphism of $R$-modules. The following are equivalent: (1) $f(M)$ is an essential submodule of $N$.
(2) For every $g: N \rightarrow O$, $gf$ injective implies $g$ is injective.

Exercise (B) Let $f: M \hookrightarrow N$ be injective with essential image. If $M$ is uniform then $N$ is uniform.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Are you saying $f^{-1}$ open sum? Thats not true or why you can set $M_{i}=f^{-1}(N_{i})$ for $i=1,2$?? @Badam Baplan $\endgroup$ – Cos May 29 at 3:16
  • 1
    $\begingroup$ @cos What is "open sum"? I'm just defining $M_1 = f^{-1}(N_1)$ and likewise for $M_2$ $\endgroup$ – Badam Baplan May 29 at 3:20
  • $\begingroup$ Sorry I got confused, think I already understand your proof but still understanding some details. I really aprecciate your throught this one @Badam Baplam $\endgroup$ – Cos May 29 at 3:31
  • 1
    $\begingroup$ @Cos Sure, feel free to ask if something is unclear. $\endgroup$ – Badam Baplan May 29 at 3:37
  • 1
    $\begingroup$ @Cos i updated and gave you some exercises to think about! $\endgroup$ – Badam Baplan May 30 at 16:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.